FERTILITY CARE IN LOW- AND MIDDLE-INCOME COUNTRIES: Public sector access to medically assisted reproduction in South Africa: a case study - Gerhardus Marthinus Boshoff; Willem Ombelet; Carin Huyser (Reproduction and Fertility)
In South Africa, approximately 10% of the calculated need for medically assisted reproduction is being met due to limited access and unequal availability of these services. To facilitate understanding of challenges associated with access to assisted reproduction, a retrospective case study spanning 6 years was performed at one public sector hospital in South Africa offering these services. Demographic profiles, including income, region of residency and access to medical insurance, of patients seeking assistance to become pregnant were investigated. Patients were categorised as those who underwent diagnostic investigations only vs those who returned for therapeutic procedures, and the difference in demographic profiles between the two groups was determined. This investigation showed that patients from the lower-income classification group, without medical insurance, tend to return for therapeutic procedures less often than those with a higher income and medical insurance, even though these low-income patients qualify for a therapeutic procedure subsidy. An inverse relationship existed where patient numbers decreased as their travel distance increased, but patients who were required to travel further for assisted reproductive therapy tended to return for these procedures more often than patients who resided closer to the medical facility. In conclusion, access to medically assisted reproduction facilities is critically undersupplied and limited in the region. In order to ease the travel distance of patients, alternative primary diagnostic routes with accessible clinics are needed. In addition, costs of therapeutic procedures in the public sector should be re-evaluated to be offered at affordable rates for marginalised patients.